2015
DOI: 10.1186/s12914-015-0054-y
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional analysis of self-efficacy and social capital in a community-based healthy village project in Santa Cruz, Bolivia

Abstract: BackgroundAn assessment of self-efficacy and social capital may have the potential to detect an effect of dynamic, complex and comprehensive collective actions in community-based health promotion. In 2003, a healthy village project was launched in Santa Cruz, Bolivia with technical assistance from the Japan International Cooperation Agency (JICA). The originally developed FORSA (Fortalecimiento de Redes de Salud) model accounted for participatory processes in which people could improve their health and well-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In their studies, Poortaghi et al 40 proved that self-efficacy was low and statistically insignificant in both the study group and control group (40 people each, 26.36±0.84 vs 28.53±0.54). In the study by Yuasa et al, 41 340 subjects were assessed on subjective level of self-efficacy, and their score was 33.5±4.5. Other research into development and promotion of health in local communities also showed a higher level of GSES.…”
Section: Discussionmentioning
confidence: 99%
“…In their studies, Poortaghi et al 40 proved that self-efficacy was low and statistically insignificant in both the study group and control group (40 people each, 26.36±0.84 vs 28.53±0.54). In the study by Yuasa et al, 41 340 subjects were assessed on subjective level of self-efficacy, and their score was 33.5±4.5. Other research into development and promotion of health in local communities also showed a higher level of GSES.…”
Section: Discussionmentioning
confidence: 99%
“…SC and self-efficacy emerged as reference points in various studies (Koçak et al. , 2013; Yuasa et al. , 2015; Wuepper and Sauer, 2016; Kannadhasan et al.…”
Section: Introductionmentioning
confidence: 99%
“…SC and self-efficacy emerged as reference points in various studies (Koçak et al, 2013;Yuasa et al, 2015;Wuepper and Sauer, 2016;Kannadhasan et al, 2018;Andersson, 2021), and well recognized as cultural traits which affect the performance of farmers (Wuepper and Sauer, 2016). Although, the relationship dynamics of these concepts seem to be narrow and localized (Tregear and Cooper, 2016).…”
mentioning
confidence: 99%
“…According to the World Bank standard, the number of people living in poverty in China has dropped from 771 million to 17 million [5]. Against the background of poverty alleviation, large private enterprises have played an important role [6]. Core reading: Winning the battle against poverty is a landmark indicator to achieve our party's first centuryold goal, and it is a hard task that must be completed to build a moderately prosperous society in an all-around way.…”
Section: Introductionmentioning
confidence: 99%